2001
DOI: 10.1530/rep.0.1220889
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the capacitation-like state of cooled boar spermatozoa with true capacitation

Abstract: ResearchCryopreserved spermatozoa demonstrate reduced conception rates compared with fresh spermatozoa when used for artificial insemination. The preliminary stage of cryopreservation of spermatozoa involves cooling to 5ЊC, during which spermatozoa experience a capacitation-like change, which may be partially responsible for the reduced conception rate observed. The aim of this study was to determine the nature of these capacitation-like changes and how much this process resembles true capacitation. Boar sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
1
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(71 citation statements)
references
References 34 publications
9
58
1
2
Order By: Relevance
“…In recent studies, effort has been focused to test whether spermatozoa membranes retain their ability to respond to oviductal signals, considering dynamic responses in spermatozoa under experimentally mimicked fertilizing conditions (Henning et al, 2012;Petrunkina et al, 2005a). Several studies have indicated that a certain subpopulation of boar spermatozoa may loose their responsiveness to the capacitating stimulus bicarbonate during hypothermic storage (Green & Watson, 2001;Guthrie & Welch, 2005;Harrison et al, 1996;Petrunkina et al, 2005b). Henning et al (2012) showed that the comparison of calcium-dependent spermatozoa responses between three different media, capacitating Tyrode's medium, (including calcium and bicarbonate), bicarbonate-free Tyrode's medium and calcium-and bicarbonate-free medium, sensitively detected storage-related changes in the spermatozoa population.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, effort has been focused to test whether spermatozoa membranes retain their ability to respond to oviductal signals, considering dynamic responses in spermatozoa under experimentally mimicked fertilizing conditions (Henning et al, 2012;Petrunkina et al, 2005a). Several studies have indicated that a certain subpopulation of boar spermatozoa may loose their responsiveness to the capacitating stimulus bicarbonate during hypothermic storage (Green & Watson, 2001;Guthrie & Welch, 2005;Harrison et al, 1996;Petrunkina et al, 2005b). Henning et al (2012) showed that the comparison of calcium-dependent spermatozoa responses between three different media, capacitating Tyrode's medium, (including calcium and bicarbonate), bicarbonate-free Tyrode's medium and calcium-and bicarbonate-free medium, sensitively detected storage-related changes in the spermatozoa population.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is believed to follow a different pathway to that of physiological capacitation. Green & Watson (2001) found that lipid bilayer fluidity and tyrosine phosphorylation signalling pathways differed between boar spermatozoa that were cooled (5 8C) and re-warmed from those that were capacitated in vitro. Variations in protein tyrosine phosphorylation patterns between in vitro capacitated and cryopreserved spermatozoa have also been demonstrated in a number of species (bull (Cormier & Bailey 2003), boar (Bravo et al 2005) and stallion (Thomas et al 2006)).…”
Section: Sperm Surface Alterations During Sperm Handlingmentioning
confidence: 97%
“…Further developments in this area would benefit from clarification of the differences between physiological sperm capacitation (see section 'Physiological alterations of the sperm surface') and handling-induced capacitation-like changes. It has already been shown that protein tyrosine phosphorylation patterns may differ (Green & Watson 2001), and as we gain further insight into the capacitation process, it is becoming unlikely that other intricate stimulation mechanisms such as cholesterol depletion, ROS-induced specific signalling of spermatozoa and removal of seminal plasma proteins from the sperm surface occur in a controlled manner during 'capacitation' induced by sperm handling as they do during physiological capacitation.…”
Section: General Conclusionmentioning
confidence: 99%
“…Chlortetracycline stain was carried out as described by Green and Watson (2001); briefly, 100 μl of filtered semen was added to 100 μl of a chlortetracycline solution and mixed for 30 s; 20 μl of glutaraldehyde solution (0.2% v/v in distilled water) was then added and mixed for 10 s. Ten microliters of this solution was put on a slide with a drop of DABCO (220 mM in glycerol, Sigma); a cover slide was gently pushed over this preparation and was protected from light. Two smears per ejaculate were prepared and 100 cells were counted from each slide classifying them according to CTC fluorescence patterns: (1) F, with uniform fluorescence over the whole head, considered characteristic of uncapacitated acrosome-intact spermatozoa; (2) B, with fluorescence-free band in the post-acrosomal region, considered characteristic of capacitated, acrosome-intact spermatozoa; or (3) AR, with almost no fluorescence over the whole head except for a band of fluorescence in the equatorial segment, considered characteristic of capacitated acrosome-reacted spermatozoa (Fraser 1995).…”
Section: Chlortetracycline Assaymentioning
confidence: 99%
“…Also, this assay has been used to assess premature capacitation during cryopreservation (Green and Watson 2001). Thus, CTC assay together to routine semen assessment tests may produce extra information to take vital decisions about the final use of spermatozoa and to improve freezing protocols.…”
Section: Introductionmentioning
confidence: 99%